Paper Review: Aplikasi DES (Deep Eutectic Solvents) sebagai Katalis Hijau - Sunarno; Aisha, Farra; Zahrina, Ida (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2022)
Deep eutectic solvents (DES) were intoduced to overcome the drawbacks of conventional catalysts (H2SO4, HCl, H3PO4, p-toluene sulfonic acid) due to several advantages; biodegradibility, cheap raw materials, high thermal and chemical stabilities, low melting point, low volatility, low toxicity, simple preparation as well as its physicochemical properties (melting point, acidity, density, viscosity, solubility and polarity) are easy to modify. DES is a mixture of two or more compounds of hydrogen bonding acceptor (HBA) and hydrogen bonding donor (HBD). The hydrogen bond formed between HBA/HBD mixture resulting to lower lattice energy thus lowering its melting point. Previous authors had reported the application of DES as reaction medium exhibit excellent catalytic activity on product yields, conversions and reusabilities. The aim of this article is to attract attention more comphrehensive studies on the utilization of DES as potential green catalyst.